Observations of rain‐induced near‐surface salinity anomalies. Issue 8 (26th August 2014) - Asher, William E.; Jessup, Andrew T.; Branch, Ruth; Clark, Dan
Abstract Vertical salinity gradients in the top few meters of the ocean surface can exist due to the freshwater input from rain. If present, surface gradients complicate comparing salinity measured at depths of a few meters to salinities retrieved using L‐band microwave radiometers such as SMOS and Aquarius. Therefore, understanding the spatial scales and the frequency of occurrence of these vertical gradients and the conditions under which they form will be important in understanding sea surface salinity maps provided by microwave radiometers. Salinity gradients in the near‐surface ocean were measured using a towed profiler that profiled salinity in the top 2 m of the ocean with a minimum measurement depth of 0.1 m. In addition, an Underway Salinity Profiling System was installed on the R/V Thomas G. Thompson. This measured near‐surface salinity at depths of 1 and 2 m. Both the towed profiler and the underway system found the occurrence of negative salinity anomalies (i.e., salinity decreasing toward the surface) was correlated with the presence of rain. The magnitude of the anomaly (i.e., the difference between salinity at 0.1 m and the salinity at 0.26 m) was proportional to the cube of the rain rate for rain rate, R, greater than 6 mm h−1. From this, for R > 15–22 mm h−1, depending on the areal extent of the salinity anomalies, rain can cause scene‐averaged salinity offsets that are as large as the accuracy goal for Aquarius of 0.1‰.